(untitled) (Research, Society and Development, 2025)
Introduction: Pediatric heart failure (HF), mainly associated with congenital and acquired heart disease, has high hospitalization and mortality rates, despite the lower incidence compared to adults. Objective: To analyze the epidemiological profile of hospitalizations for heart failure in children and adolescents in Brazil between 2015 and 2024. Methodology: Cross-sectional, descriptive study, based on data from the SUS Hospital Information System (DATASUS). Hospitalizations of patients aged 0 to 19 years with a diagnosis of HF (ICD-10: I50) were included. The analysis was performed in Microsoft Excel using descriptive statistics. Results: A total of 1,989,711 hospitalizations for HF were recorded in Brazil, of which 31,277 (1.6%) referred to the pediatric population. The age extremes (<1 year and 15–19 years) concentrated the majority of cases, with 39.4% and 17.3%, respectively. Hospitalizations in children aged 1 to 4 years accounted for 20.1%, and in the groups aged 5 to 9 years and 10 to 14 years, 11.5% and 11.8%. Conclusion: Although less prevalent, pediatric HF imposes a significant burden on the health system, with a predominance in infants and adolescents. The study reinforces the importance of early detection and effective management strategies to reduce hospitalizations and adverse outcomes in this population.